Unidade Local de Proteção Civil da Junta da Freguesia de Aljezur - Gomes, Artur (2020)
As president of the Aljezur Villa's Council and Official in the Humanitarian Association of Volunteer Firefighters of Aljezur, it makes perfect sense to propose and develop a functional organization model for a Civil Protection Locality in the Villa of Aljezur. In this way, I can contribute to the improvement of the protection and rescue services that we may all need as a function of their employment relationship with the structures and contributing to a more resilient territory. During emergency situations, local Council authorities are the first in the line of response, sometimes with a great responsibility but insufficient capacity to deal with the circumstances. They are also on the front line when it comes to planning, anticipating, and reducing the risks and hazards of major accidents or disasters, implemented and working on alert and warning systems. In most cases, the review of responsibilities and allocation of resources is necessary to enhance the capacities of local Council authorities to respond to all these challenges. Thus, this work intends to present a standard model of organization and functioning of the territorial context of the Local Councils, contributing to prevent or minimize situations of risk and mitigate their effects. Risk prevention and mitigation strategies to be implemented in the target area, hazards reduction or vulnerability, as well as recommendations and proposals for the application of good resilience practices that Local Civil Protection Unit of Aljezur, where projects and partnerships will be developed. The recommendations will be defined and listed in order to increase the resilience of this territory.